A scaling-up strategy supporting the expansion of integrated care: a study protocol. Issue 3 (10th October 2018) - Grooten, Liset; Alexandru, Cristina-Adriana; Alhambra-Borrás, Tamara; Anderson, Stuart; Avolio, Francesca; Valia Cotanda, Elisa; Gütter, Zdenek; Henderson, Donna; Kassberg, Ann-Charlotte; de Manuel Keenoy, Esteban; Lange, Marc; Lundgren, Lisa; et al.
Abstract : Purpose: To ensure that more people will benefit from integrated care initiatives, scaling-up of successful initiatives is the way forward. However, new challenges present themselves as knowledge on how to achieve successful large-scale implementation is scarce. The EU-funded project SCIROCCO uses a step-based scaling-up strategy to explore what to scale-up, and how to scale-up integrated care initiatives by matching the complementary strengths and weaknesses of five European regions involved in integrated care. The purpose of this paper is to describe a multi-method evaluation protocol designed to understand what factors influence the implementation of the SCIROCCO strategy to support the scaling-up of integrated care. Design/methodology/approach: The first part of the protocol focuses on the assessment of the implementation fidelity of the SCIROCCO step-based strategy. The objective is to gain insight in whether the step-based strategy is implemented as it was designed to explore what works and does not work when implementing the scaling-up strategy. The second part concerns a realist evaluation to examine what it is about the SCIROCCO's strategy that works for whom, why, how and in which circumstances when scaling-up integrated care. Findings: The intended study will provide valuable information on the implementation of the scaling-up strategy which will help to explain for what specific reasons the implementation succeeds and will facilitate further improvement of project outcomes. Originality/value: The expected insights could be useful to guide the development, implementation and evaluation of future scaling-up strategies to advance the change towards more sustainable health and care systems.